Parent’s experience of perinatal post-mortem following stillbirth: A mixed methods study - Henderson, J; Redshaw, M (Public Library of Science, 2017)
Objectives To analyse quantitative and qualitative data, to describe the experience of parents in relation to post-mortem following stillbirth, looking at offer and uptake of post-mortem, information-giving, the type of post-mortem carried out, receiving the results and any sociodemographic differences in care practices in relation to post-mortem. Design Secondary analysis of a postal survey which included both open and closed questions allowing for a mixed methods study design. Population Random sample of women who experienced a stillbirth in 2013. Methods A sample of women who experienced a stillbirth in 2013 were selected by staff at the Office for National Statistics and sent a letter and information leaflet about the study followed by a postal questionnaire. The questionnaire included questions about pregnancy, labour and birth, the postnatal period, the time at which the baby died, and also asked about the post-mortem process. Results Completed questionnaires were received from 477 women. Overall, 95% of women were asked for consent to a post-mortem, almost half prior to birth, and half by a consultant. The majority of women received written information and felt sufficiently informed, and agreed to a full post-mortem. A third of women had to wait longer than 12 weeks for the post-mortem result and this was the most common theme in the free text comments. Women also commented on the manner of being asked for consent, and wrote about issues related to communication and support. There were significant differences between sociodemographic groups in many of these factors. Conclusions The inconsistencies in offer and consent to post-mortem following stillbirth suggest inequality in this area. The amount of time that many parents have to wait for post-mortem results is unacceptable and should be prioritised for improvement.